Development of an Innovative Physical Education Learning Model Based on Modified Basic Badminton Techniques to Increase Students' Active Participation - Ishak, Muhammad; Adil, Ahmad (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This study aims to develop an innovative Physical Education (PE) learning model based on modifications to basic badminton techniques to increase active student participation at SMK Negeri 7 Makassar. The study employed a Research and Development (R&D) method, encompassing needs analysis, model design, expert validation, limited trials, and effectiveness evaluation. The study sample consisted of 20 tenth-grade students selected using a purposive sampling technique. Data were collected through active participant observation, badminton skills tests (pretest–posttest), and student response questionnaires. Data analysis was conducted using descriptive statistics and thematic qualitative analysis. The results showed that the learning model based on modifications to basic badminton techniques was effective in increasing student active participation across four key indicators: physical, emotional, cognitive, and social engagement. The 51.9% increase in active participation indicates that this model is able to create a more engaging and inclusive learning environment. Furthermore, there was a 60.3% increase in mastery of basic badminton techniques, indicating that modifications to the equipment, court, and rules of the game helped students understand skills in a gradual and contextual manner. Student responses to the model were also very positive, with an average score of 4.60, indicating that students felt comfortable, motivated, and actively engaged during the learning process. Overall, this learning model is feasible for implementation in physical education (PJOK) learning and has the potential to be developed in other school contexts. Further research is recommended using a larger sample size and a comparative experimental design.